BIOLOGIA E ETOLOGIA DE Coelomera rachia (COL; CHRYSOMELIDAE) EM LABORATÓRIO - Dorval, Alberto; Peres Filho, Otávio; Berti Filho, Evoneo (REVISTA DE AGRICULTURA, 2016)
BIOLOGIA E ETOLOGIA DE Coelomera rachia (COL; CHRYSOMELIDAE) EM LABORATÓRIO